End-to-end game development : creating independent serious games and simulations from start to finish - Iuppa, Nicholas V. (Focal Press, 2010)
You're part of a new venture, an independent gaming company, and you are about to undertake your first development project. The client wants a serious game, one with instructional goals and assessment metrics. Or you may be in a position to green light such a project yourself, believing that it can advance your organization's mission and goals. This book provides a proven process to take an independent game project from start to finish. In order to build a successful game, you need to wear many hats. There are graphic artists, software engineers, designers, producers, marketers - all take part in the process at various (coordinated) stages, and the end result is hopefully a successful game. Veteran game producers and writers (Iuppa and Borst) cover all of these areas for you, with step by step instructions and checklists to get the work done. The final section of the book offers a series of case studies from REAL indy games that have been developed and launched succesfully, and show exactly how the principles outlined in the book can be applied to real world products. The book's associated author web site offers ancillary materials & references as well as serious game demos and presentations. *Step-by-step no-nonsense approach to developing games from start to finish (graphic arts, software engineering, designing, producing, marketing all covered). Indy game developers will gain a clear understanding of what's involved. *Demonstrates a proven process for meshing gameplay and story to create an immersive experience for the player. *Even experienced game developers will benefit from some of the coverage, especially: setting curriculum goals, setting client expectations, and client management. *Authors are authorities in the field with decades of experience in designing and producing entertainment and educational media. Their games and other instructional designs have received numerous awards and accolades and they have held executive positions in training organizations at Fortune 500 companies. *Accompanying web site offers tools and helpful add-ons related to the book, including a serious game demo and presentation.